Immunohistology of oestrogen receptor and D5 antigen in breast cancer: correlation with oestrogen receptor content of adjacent cryostat sections assayed by radioligand binding and enzyme immunoassay. Issue 7 (July 1987) - Giri, D D; Dangerfield, V J; Lonsdale, R; Rogers, K; Underwood, J C
Abstract : Two monoclonal antibodies recognising epitopes associated with oestrogen receptor protein were evaluated against the assayable soluble oestrogen receptor concentration in a series of 149 breast carcinomas. One antibody (anti-ER) recognises the hormone binding unit of oestrogen receptor and gives nuclear staining; the other antibody (anti-D5) was raised to a component of soluble oestrogen receptor and gives cytoplasmic staining. To minimise variations attributable to tumour heterogeneity and sampling error immunohistology using the two monoclonal antibodies, radioligand binding assays, enzyme immunoassays, and quantitative histology were done on adjacent frozen sections. Thirty nine per cent, 48%, 54%, and 43% of the tumours were found to be oestrogen receptor positive by radioligand binding assay, anti-ER and anti-D5 immunohistology, and enzyme immunoassay, respectively. Strong correlations (p less than 0.0005) were found between anti-ER immunohistology and the radioligand binding assay. Only weak correlations were found between anti-D5 immunohistology and the results of other assay methods for oestrogen receptor. Nuclear staining of human breast cancers with the anti-ER monoclonal antibody thus seems to be an acceptable alternative to biochemical assays, with the additional advantage of showing intercellular and regional heterogeneity for oestrogen receptor content.